An integrative analysis revealing cuproptosis-related lncRNAs signature as a novel prognostic biomarker in hepatocellular carcinoma - Chen, Xilang; Sun, Mengyu; Feng, Weibo; Chen, Jie; Ji, Xiaoyu; Xie, Meng; Huang, Wenjie; Chen, Xiaoping; Zhang, Bixiang; Nie, Yongzhan; Fan, Daiming; Wu, Kaichun; et al. (Frontiers in Genetics, 2023)
Primary liver cancer ranked the sixth most common cancer in terms of incidence and the fourth leading cause of cancer-related death worldwide, the incidence rates and mortality rates of liver cancer were much higher in transitioned countries, especially in East Asia and Africa.Hepatocellular carcinoma (HCC), the dominant type of primary liver malignancies, is often found at an advanced stage and thus has a poor prognosis. Cuproptosis is a newly defined form of cell death, which is distinct from regulated cell death. Whether cuproptosis involved in hepatocellular carcinoma (HCC) remains elusive. In our work, we demonstrated that high expression of DLAT correlated to metastasis of HCC cells and indicated poor prognosis for HCC patients. We established and validated a cuproptosis-related lncRNAs (CRLs) prognostic signature based on four identified CRLs. We also developed a nomogram based on risk model to predict the clinical outcomes of individual HCC patients. The correlation between the risk model and immune cells, expression of immune checkpoint genes, and sensitivity of clinical treatment has also been explored. Finally, GSEA was performed to investigate the pathways enriched in different risk groups. In conclusion, CRLs prognostic signature can be a novel predictor of HCC patients’ prognosis and provide references to the therapeutic decision.